EFFECTS OF ANTHRACYCLINES ON LEFT VENTRICULAR FUNCTION ON BREAST CANCER PATIENTS (Tạp chí Y học Cộng đồng, 2022)
Objective: To investigate the effect of Anthracyclines on left ventricular function onbreast cancer patients at Thong Nhat Hospital. Objects and methods: A prospectivedescriptive study on 43 patients with breast cancer treated with Anthracyclines with4 to 6 cycles as determined by the clinical doctor at Thong Nhat Hospital. Results:Percentage of left ventricular ejection, total deformation of the vertical systolic stagedecreased significantly after treatment: EF before and after treatment were 60.23± 3.46 and 59.44 ± 3,67 (%), respectively; GLS before and after treatment were-20.01 ± 1.62 and -19.14 ± 1.82 (%), respectively. The incidence of cardiotoxicitywas 6.98%. The proportion of patients with subclinical left ventricular dysfunctionwas 23.26%. After treatment, the proportion of respectively. The proportion ofpatients with subclinical systolic dysfunction was higher in the decreased diastolicfunction group compared to the group with normal diastolic function. Patients withnormal diastolic function after treatment decreased, the proportion of patients withdiastolic dysfunction increased significantly, accounting for 41.86% and 58.14%No association was found between the type of anthracycline used, also diseasestage and the effect of anthracycline on left ventricular function. Conclusion: Leftventricular ejection fraction, total deformation of the vertical systolic stage reduced.The prevalence of cardiac toxicity and subclinical left ventricular dysfunction weremoderate. After treatment, the proportion of patients with normal diastolic functiondecreased, the diastolic dysfunction increased. There was no relationship between thetype of Anthracycline used, also the disease stage and the effect of Anthracycline onleft ventricular function.
Keywords: Breast cancer, left ventricular function, Anthracyclines.